Kultura wobec praksis w ujęciu antropologicznym - Saja, Krystian (Kultura-Społeczeństwo-Edukacja, 2015)
The contemporary anthropology seems to be extremely superficial. Anthropologists do not pay attention to how the studied artifacts arise in the human mind. They tend to watch communities associate with these artifacts, analyze customs, religion, inventions, and other artifacts, but it is not sufficient to achieve the effect of objectivity. Cultural relativism is chosen as a tool to deal with them. It seems that the starting point for a complete rejection of ethnocentrism is the distinction b e tween the cultural sphere praxis and fitness. In turn, in order to achieve the cultural unification one should pay c lose attention to the so-called first principles. The aim of this article is to prove the existence of the first principles as indicators of how do they work in culture. Rules are independent of space and time, and, moreover, they are based in our culture and how we perceive the world around us. We may observe that these rules have existed in human culture from its beginning due to the fact that it was based on them.